2017
DOI: 10.4103/1793-5482.145086
|View full text |Cite
|
Sign up to set email alerts
|

Primary intracranial choriocarcinoma presenting as a ring-enhancing lesion: A case report and review of literature

Abstract: We report here a rare case of primary intracranial choriocarcinoma without evidence of tumor elsewhere, presenting as a ring-enhancing lesion managed successfully in our institute (Grant Medical College and Sir J. J. Group of Hospitals, Mumbai, Maharashtra, India). A 22-year-old, right-handed housewife presented with complaints of headache, vomiting, generalized tonic–clonic seizures, and right upper limb weakness of short duration. On neurological examination, the patient was conscious, cooperative, well-orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…As choriocarcinomas are very rare in the CNS, no clinical trials have reported the treatment of these tumors, except the standard treatment strategies. For this reason, the neurosurgeons have adopted surgical strategies for the treatment (4,5,10,11). As shown in this study, the tendency of the surgeons was mostly toward surgical treatment, but no sig-nificant difference between surgical and nonsurgical procedures was found.…”
Section: Discussionmentioning
confidence: 99%
“…As choriocarcinomas are very rare in the CNS, no clinical trials have reported the treatment of these tumors, except the standard treatment strategies. For this reason, the neurosurgeons have adopted surgical strategies for the treatment (4,5,10,11). As shown in this study, the tendency of the surgeons was mostly toward surgical treatment, but no sig-nificant difference between surgical and nonsurgical procedures was found.…”
Section: Discussionmentioning
confidence: 99%